2014
DOI: 10.1021/ma402454j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Composition on the Phase Behavior of Ion-Containing Block Copolymers Studied by a Minimal Lattice Model

Abstract: We performed Monte Carlo simulations using a minimal lattice model with short-range interactions modeled using Flory−Huggins interactions parameters, χ, to investigate morphology of ioncontaining A−B diblock copolymers. A fraction of the segments in the A block, p, were ionic (labeled S) while the B block segments were nonionic (p was held fixed at 0.588). The dielectric constants of the polymers is assumed to be low, and thus charge dissociation effects are negligible. The magnitude of the χ between ion and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 38 publications
3
23
0
Order By: Relevance
“…Brownian dynamics simulations of a block copolymer where the charged block accounts for 25% of the component monomers match the results of the field theory simulations when the dielectric constant is low; however, for high dielectric constant materials, increased charge promotes phase mixing . Lattice Monte Carlo simulations for symmetric diblocks show the presence of cylindrical, gyroid, hexagonally perforated lamellar, and lamellar phases depending on the degree of charge, the value of χ , and the overall chain length …”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…Brownian dynamics simulations of a block copolymer where the charged block accounts for 25% of the component monomers match the results of the field theory simulations when the dielectric constant is low; however, for high dielectric constant materials, increased charge promotes phase mixing . Lattice Monte Carlo simulations for symmetric diblocks show the presence of cylindrical, gyroid, hexagonally perforated lamellar, and lamellar phases depending on the degree of charge, the value of χ , and the overall chain length …”
Section: Introductionmentioning
confidence: 56%
“…There have been several different approaches to modeling the phase behavior of low dielectric constant block copolymers with salt or charge, which have resulted in different predictions for the expected phase behavior. Knychala et al 33,34 used a Monte Carlo simulation approach where six v parameters were defined between three different monomers (two uncharged, one charged) with the highest values of v between the charged and uncharged monomers; they found that the effective interaction depended on the square of the fraction of charged monomers (p) and that the strong segregation regime was dominated by lamellar phases caused by a high degree of chain stretching (p 2 vN values of 40 and above for the compositions studied here), FULL PAPER inconsistent with our experimental observations. Goswami et al 32 and Sing et al 30,31 both developed approaches that account for Coulombic interactions: Goswami using an explicit Coulomb potential in a Brownian dynamics simulation and Sing by using a coupled liquid state and selfconsistent field theory simulation.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…One example would be poly(styrenesulfonate‐ block ‐polymethylbutylene) in which a random selection of the polystyrene monomers are sulfonated. Experimental studies as well as Monte Carlo simulations have shown that this system displays interesting phase behaviors . It would be interesting to explore the phase behavior of random copolymers with a non‐Markovian sequence distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies as well as Monte Carlo simulations have shown that this system displays interesting phase behaviors. [5][6][7] It would be interesting to explore the phase behavior of random copolymers with a non-Markovian sequence distribution.…”
Section: Introductionmentioning
confidence: 99%